The Effect of Packaging Type and Temperature on the Characteristics of Habang Seasonings During Storage - Dessy Maulidya Maharani; Tanwirul Millati; Dhebora Shofia Hercillena (TROPICAL WETLAND JOURNAL, 2022)
The red traditional South Kalimantan cooking spice indicates that the seasoning has a deep red appearance. Although the habang cooking seasoning has a dark red appearance with the main ingredient red chili, this spice does not have a spicy taste but tends to taste sweet. This study aimed to determine the effect of different packaging and storage temperatures on the spice’s characteristics. This study used RBD method with 2 factors and 2 replications. Factor A is packaging variation and B is storage temperature. These observations included chemical tests, total microorganism tests, and sensory tests. Chemical tests and microorganisms were analyzed by the ANOVA and followed by the DMRT. Sensory test data were analyzed by the Kruskal Wallis and followed by the Post Hoc Test. Determination of the best results used the ranking method weighting. The results showed the characteristics were changed during storage. water content, peroxide number, and total microorganisms were increased in line with fat content and pH decreased. Sensitively, Habang cooking spices decreased in aroma, color, and viscosity during storage. The best Habang cooking seasoning was found in the use of cold temperature aluminum foil packaging on the 4th day of storage with a total parameter value of 8,224 and a total value of 30,195, chemical characteristics in the form of the water content of 31.46±0.02, a fat content of 69.67±0, 81, the pH value is 4.26±0.02, and the peroxide value is 3.15±0.06.